Determination of Menbutone: Development and Validation of a Sensitive HPLC Assay according to the European Medicines Agency Guideline - Cristina López; Raquel Díez; José M. Rodríguez; Matilde Sierra; Juan J. García; Nélida Fernández; M. José Diez; Ana M. Sahagún (Separations, 2022)
Menbutone is often used to stimulate the hepato-digestive activity in case of digestive disorders and hepatic insufficiency in different species (cattle, sheep, goats, pigs, horses, dogs) because it has choleretic and cholagogue effects and increases gastric and pancreatic juices. The objective was to develop and validate an HPLC method to quantify menbutone in sheep plasma using sparfloxacin as internal standard. The HPLC mobile phase consisted of acetonitrile:monopotassium phosphate solution. The method was validated according to EMA guideline (EMEA/CHMP/EWP/192217/2009). Mean retention times of menbutone and sparfloxacin were 4.5 and 2.2 min, respectively. The method met all specifications of the EMA guideline, being selective and linear in the range of 0.2–100 µg/mL (R2 ≥ 0.99). The within-run precision range was 0.19–8.21%, with an accuracy of 102.99–119.52% for the lower limit of quantitation (LLOQ). For the other values (LOW, MED, HIGH) the precision range was 0.01–4.77%, with an accuracy of 85.17–109.67%. The LLOQ was 0.2 µg/mL, and no interference from the biological matrix was found. Stability of menbutone in the biological matrix at different storage conditions was also demonstrated. Thus, the method can be used to determine menbutone concentrations in plasma sheep in different types of studies.